2017
DOI: 10.1115/1.4037988
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of a Pump–Turbine Transient Load Following Process in Pump Mode

Abstract: This paper presents the simulation of the dynamic behavior of variable speed pump–turbine. A power reduction scenario at constant wicket gate opening was numerically analyzed from 100% to 93% rpm corresponding to a power reduction from full load to about 70% with a ramp rate of 1.5% per second. The flow field analysis led to the onset and development of unsteady phenomena progressively evolving in an organized rotating partial stall during the pump power reduction. These phenomena were characterized by frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Furthermore, the study by Eichhorn et al [3] has shown that numerical analysis can predict runner stress with sufficient accuracy within stationary load points, even if unsteady flow is present. However, reproducing transient events-such as the load rejection by Jakobsen et al [10] and Pavesi et al [11] or the start-up simulated by Minakov et al [12] and Nicolle et al [13]-is still challenging. Especially in the case of a prototype machine, long simulation times and the complexity of the physics involved paired with a lack of validation cases leads to many difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the study by Eichhorn et al [3] has shown that numerical analysis can predict runner stress with sufficient accuracy within stationary load points, even if unsteady flow is present. However, reproducing transient events-such as the load rejection by Jakobsen et al [10] and Pavesi et al [11] or the start-up simulated by Minakov et al [12] and Nicolle et al [13]-is still challenging. Especially in the case of a prototype machine, long simulation times and the complexity of the physics involved paired with a lack of validation cases leads to many difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the hydraulic turbines have to operate over a wide range [2,3] under a fast change of the parameters to compensate the fluctuating part delivered in the electrical grid by the renewable energies. Several times, these requirements implied transient phenomena (e.g., load acceptance, load rejection, start-stop, emergency shutdown, spin no load, total load rejection) in operation [4][5][6][7]. Along the upstream passage of the hydraulic turbine, the potential energy of the water available in the upper tank is converted into kinetic energy.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, three dimensional (3D) numerical simulation methods that are based on computational fluid dynamics (CFD) have been increasingly applied for evaluating the transient characteristics of hydraulic turbines [26,27]. For example, Pavesi et al [28] conducted numerical simulations of a pump-turbine during the transient load following process in pump mode, and a full 3D flow structure was observed in the wicket gate channel, owing to boundary layer separation and stalling at lower rotational speeds. Li et al [29] simulated the transient guide vane closure process for a pump-turbine that was operated in pump mode, and confirmed that the dynamic instabilities that were observed at the end of the closure process originated from severe hydraulic variations that occurred in the guide vanes.…”
Section: Introductionmentioning
confidence: 99%